Identifikasi makrozoobentos sebagai bioindikator di perairan sungai Buper Bumi Perkemahan Bedengan - Ardiansyah, Moch Syaddad (Maliki Interdisciplinary Journal, 2024)
Macrozoobenthos are organisms that live at the bottom of the water in the sediment of the bottom of the water. Macrozoobenthos can be used as a bioindicator to determine environmental quality in aquatic ecosystems. The use of macrozoobenthos as a bioindicator is based on differences in the ability of macrozoobenthos to respond to changes in several environmental parameters. Macrozobenthos can be used as a bioindicator of water quality in the Buper river at Bedengan Campground. Therefore, it is important to identify macrozoobenthos diversity as a bioindicator of water quality in the Buper River at Bedengan Campground. Macrozoobenthos sampling uses a manual method by collecting several rock samples at the bottom of the water. The macrozoobenthos found in the Bedengan River in Malang consists of 3 classes, 3 orders and 3 families. The macrozoobenthos found in the plot describes the condition of the environment or area used for sampling in the research. The existence of these three macrozoobenthos families indicates that the water quality in the Bedengan River, Malang, is quite good.